Determination of volumetric shrinkage of thermally cured thermosets using video-imaging. (February 2016) - Exner, Wibke; Kühn, Alexandra; Szewieczek, Artur; Opitz, Mark; Mahrholz, Thorsten; Sinapius, Michael; Wierach, Peter
Abstract: Video-imaging is one method of analyzing the shrinkage of resins. For the measurement, a drop of resin is placed near an illumination source and its contour is imaged from the front with a camera. This paper presents a further development, detailed investigation and verification of this technique to analyze the chemical shrinkage of thermally cured epoxy resins during cure. A new cylindrical sample holder was developed which enables the automated detection of the baseline, as well as defining the scale within the pictures. In a test series, the resin's volume was varied, as well as its contour. The findings confirm that the measured volume shrinkage is independent of the drop shape. Finally, the obtained shrinkage results were verified and evaluated in comparison with values measured by a mercury dilatometer and a rheometer. The shrinkage results of the investigated new method are in good accordance with the more established methods.